Analisis Kesalahan Penulisan Latar Belakang pada Projek Mini Arikel Ilmiah Mahasiswa Universitas Pelita Bangsa Prodi BKPI Angkatan 2022 - Muktiali, Saiful; Ismamudi, Ismamudi; Nugroho, Djoko; Nenda, Nenda (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
Errors in academic writing have a strong impact on the reader, usually because there is a misunderstanding between the writer and the reader, and the main idea conveyed does not reach the writer. Therefore, this research aims to explain: (1) Forms of errors in the use of the Indonesian Spelling Guide (PUEBI), including errors in letters, words, punctuation, conjunctions, loan words, sentences and paragraphs. (2) Factors causing errors in the scientific article mini project for BKPI students class of 2022 at Pelita Bangsa University. (3) Efforts to eliminate errors in the use of the Indonesian Spelling Guide (PUEBI). This research is a qualitative descriptive research with a content analysis approach using a sample of 15 mini scientific articles from BKPI Pelita Bangsa University students class of 2022. The results of this research are as follows. First, the types of phonetic errors found in the 2022 BKPI 2022 Pelita Bangsa University student scientific work mini project included 11.33% errors in the use of capital letters, 4.00% errors in word spelling, 4.76% errors in connecting words, and errors in words. front as much as 23.33%, including punctuation errors 57.33%. Second, the factors that cause errors in the use of the Indonesian Spelling Guide (PUEBI) in students' scientific article projects are students' lack of mastery of language rules, inaccuracies in writing, students' lack of motivation to write; rules regarding vocabulary. Third, efforts were made to eliminate errors in the use of the Indonesian Spelling Guide (PUEBI) in scientific mini-articles. This includes implementing writing learning using a process approach, increasing students' mastery of language rules through reading, and improving writing skills and practice.Keywords: Writing Errors, Scientific Articles, Students.